Borehole radar system analysis in stratified geological systems applied to imaging of platiniferous reefs in the bushveld igneous - Herselman, Paul Le Roux (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2003.